Cathode wire for electric dust remover and preparation method of cathode wire
By preparing nanoceramic coating on the cathode line of the electro-dust collector, the problem of cathode line accumulation is solved, the dust removal efficiency and corrosion resistance are improved, and the process cost is reduced.
Patent Information
- Application Number
- CN202411356182.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-18
AI Technical Summary
The cathode line of the electro-dust collector is severely ash, resulting in a decrease in dust removal efficiency. The existing solutions such as vibration devices and manual cleaning have safety hazards and low efficiency.
A nanoceramic coating is prepared on the surface of the cathode line, and a coating with anti-gravel and corrosion resistance is formed by phosphating treatment and penetration and curing of the nanoceramic coating.
Effectively prevent cathode lines from ash accumulation, improve dust removal efficiency, reduce process costs, and enhance the corrosion resistance and conductivity of cathode lines.
Smart Images

Figure CN119456208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flue gas pollutant treatment, and particularly relates to a cathode wire for an electrostatic precipitator and a preparation method thereof. Background Art
[0002] Electrostatic precipitators are widely used in flue gas treatment, with advantages such as large processing flow, low energy consumption, small resistance loss and easy maintenance. After the ultra-low emission transformation, new requirements are put forward for the flue gas emission time and smoke dust emission. Therefore, it is very important to achieve long-term stable and efficient operation of the electrostatic precipitator to achieve standard smoke dust emission. In actual operation, the adhesion of dust on the anode plate and cathode wire of the electrostatic precipitator is a common problem at present. In particular, due to the excessive ammonia injection in the denitrification process, the amount of ammonia escape in the flue gas increases, forming a large amount of highly viscous ammonium bisulfate, causing dust accumulation on the plates and wires. Severe dust accumulation can reach 10mm in thickness, and the texture is hard and dense, and cannot be removed by vibration. Dust accumulation on the anode plate can easily lead to back corona phenomenon, resulting in a decrease in secondary voltage, and dust accumulation on the cathode wire will induce corona closure phenomenon and lead to a decrease in secondary current. Both phenomena will lead to an increase in the outlet dust concentration and a decrease in the efficiency of the dust collector.
[0003] In order to solve the problem of dust accumulation on the cathode wire of the electrostatic precipitator, in actual production, the main solution is to set up a vibrating device for periodic vibration to remove the dust. If it cannot be removed by vibration, the dust accumulation is cleaned manually during maintenance. Under normal circumstances, the dust on the cathode wire is relatively soft, and most of it can fall off by itself after vibration. However, the cathode wire of some electrostatic precipitators is seriously covered with dust, and the ash balls are relatively hard, especially in the thorn head part, which is seriously covered with dust and cannot be removed by vibration. When removing the dust manually, since the distance between the cathode wire and the anode plate is very narrow, usually only 200-225mm, during maintenance, the staff needs to perform comprehensive maintenance and maintenance of the plates and wires, clean the dust accumulation, etc. in a narrow space. During maintenance, the movement of personnel is extremely inconvenient, the risk of falling is high, and the cleaning quality cannot be guaranteed, which has a great impact on the dust removal efficiency of the electrostatic precipitator.
[0004] In addition to periodic vibration and manual cleaning of dust accumulation, there are some new methods to solve the dust accumulation of cathode wires. For example, the Chinese patent application with application number CN202111267761.X solves the dust accumulation problem by setting a heating mechanism inside the cathode wire, but its structure is complex and difficult to implement. The Chinese patent application with application number CN202310372999.1 improves the corrosion resistance and corona discharge efficiency of the cathode wire by adopting the method of hot-dip galvanizing the cathode wire as a whole. The Chinese patent with application number CN202210872325.3 uses the method of electrostatic spraying of organic coating to protect the cathode wire, which improves the corrosion resistance of the cathode wire, but has limited effect on dust prevention. The Chinese patent with application number CN200820135620.6 uses Teflon coating to improve the anti-stickiness of the cathode wire surface, but Teflon is poorly bonded to the substrate, the coating is easy to fall off, and the Teflon material is not conductive, which affects the discharge effect.
[0005] Therefore, how to improve the anti-dust deposition performance of the cathode line without reducing the original discharge capacity is a problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a cathode wire for an electrostatic precipitator and a preparation method thereof, wherein a layer of nano-ceramic coating is prepared on the surface of the cathode wire to achieve dust prevention and corrosion resistance.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] One of the purposes of the present invention is to provide a method for preparing a cathode line for an electrostatic precipitator, comprising the following steps:
[0009] S1: Phosphating the cathode wire to form a phosphating film with a microporous structure on its surface;
[0010] S2: coating the nano-ceramic coating on the cathode wire treated in step S1, so that the nano-ceramic coating penetrates into the microporous structure of the phosphating film in a wet film state; the raw materials of the nano-ceramic coating include nano-particles and solvents;
[0011] S3: baking the cathode wire treated in step S2 at 90-120° C. for 20-40 min to solidify the coating on the surface of the cathode wire to form a nano ceramic coating with a thickness of 10-50 μm, thereby obtaining the cathode wire for the electrostatic precipitator.
[0012] Furthermore, in step S1, before the cathode wire is subjected to phosphating treatment, the cathode wire is also subjected to pretreatment, wherein the pretreatment includes degreasing, pickling and water washing of the cathode wire to remove rust, grease and oxide film on the surface of the cathode wire. The specific process of the pretreatment is as follows:
[0013] S11: immerse the cathode wire in a first degreasing tank at 65°C for 6 minutes, then immerse it in a second degreasing tank for 3 minutes, and wash it twice to complete degreasing; the tank liquid in the degreasing tank is 50g / L of degreasing agent;
[0014] S12: Immerse the degreased and deoiled cathode wire in a pickling tank at 28°C for 1 minute, and then rinse with water twice to complete the pickling treatment.
[0015] Furthermore, in step S2, the nanoparticles are one or a mixture of nano-aluminum oxide particles, nano-titanium oxide particles, nano-zirconium oxide particles, and nano-silicon oxide particles.
[0016] Furthermore, the nanoparticles are a mixture of nano-silicon oxide particles and one or more of nano-aluminum oxide particles, nano-titanium oxide particles, and nano-zirconium oxide particles, and the weight ratio of the nano-silicon oxide particles to the other nanoparticles is (1-8):1.
[0017] Furthermore, the nanoparticles are a mixture of nano silicon oxide particles and nano titanium oxide particles, and the weight ratio of the nano silicon oxide particles to the nano titanium oxide particles is 5:1.
[0018] Furthermore, the raw material of the nano-ceramic coating also includes a thin layer of graphene, and the mass percentage of the graphene in the nano-ceramic coating is 1-5wt%.
[0019] Furthermore, the solvent is one or a combination of anhydrous ethanol, methanol, isopropanol, n-heptane, n-octane, benzene, toluene, xylene, ethylbenzene, and naphtha.
[0020] Furthermore, in step S2, the coating is applied within 48 hours after the phosphating treatment.
[0021] A second object of the present invention is to provide a cathode wire for an electrostatic precipitator, which is prepared by any of the above-mentioned methods for preparing a cathode wire for an electrostatic precipitator.
[0022] Furthermore, the cathode wire comprises a supporting round steel and a plurality of needles welded on the supporting round steel, the surfaces of the supporting round steel and the needles are provided with a phosphate film, and the surface of the phosphate film is provided with a nano-ceramic coating.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a method for preparing a cathode wire for an electrostatic precipitator, wherein the cathode wire is subjected to phosphating treatment and coating. The nano-ceramic coating used in the present invention can penetrate well into the microporous structure inside the phosphating film through capillary action in a wet film state, and can further improve the corrosion resistance of the coating through the action of chemical bonds, and improve the bonding strength between the coating and the substrate.
[0025] 2. The nano-ceramic coating of the present invention also has excellent anti-dust and easy-to-clean properties, and is not prone to cathode wire wrapping. The nano-ceramic coating is added with a thin layer of graphene, which has good electrical conductivity and good corona discharge effect. As a conductive filler for the cathode wire coating, it can increase the conductive effect of the cathode wire and improve its corrosion resistance and wear resistance without affecting the discharge effect of the cathode wire.
[0026] 3. The nano ceramic coating used in the present invention can be baked at a relatively low temperature so that the cured coating has good performance, which can greatly reduce the process and production costs.
[0027] 4. In the present invention, before the cathode wire is phosphated, the cathode wire is also pretreated, and the pretreatment includes degreasing and deoiling, pickling and water washing of the cathode wire to remove rust, grease and oxide film on the surface of the cathode wire. The degreasing and deoiling can remove oil stains attached to the surface of the cathode wire and residues such as waste chips and dust generated during the processing; the pickling treatment can eliminate rust and oxide film on the surface of the cathode wire to expose a clean activated surface; the water washing step can remove residual chemicals on the surface of the workpiece.
[0028] 5. In the present invention, the problem of poor toughness and easy cracking of inorganic nano coatings is solved by adjusting the addition ratio of inorganic nanoparticles. Compared with traditional organic coatings, the inorganic nano ceramic coating of the present invention has the characteristics of high hardness, good corrosion resistance and self-cleaning. In addition, the present invention also uses nano alumina particles, nano silicon oxide particles and other nano particles with easy cleaning, high hardness and high corrosion resistance, which can improve the anti-sticking, wear resistance and corrosion resistance of the coating, and adjust the toughness of the coating by adjusting the addition ratio of each nanoparticle to avoid defects such as cracking.
[0029] 6. In the present invention, the inorganic nano-ceramic coating used has a lower curing temperature and a shorter curing time. This solves the problem that traditional organic coatings, due to the presence of a large amount of high molecular polymers, generally require a high temperature of 180°C or even above 200°C for more than half an hour to cure the coating, and long-term high-temperature baking will cause a certain degree of deformation of the workpiece, resulting in a decrease in yield. The inorganic nano-ceramic coating used in the present invention can be cured at a temperature as low as 100°C for 20 minutes, which will not affect the workpiece and can save a lot of energy consumption for high-temperature curing.
[0030] 7. In the present invention, the ceramic coating used is prepared by making a sol from nanoparticles, a thin layer of graphene and a solvent, and then can be sprayed, poured, dipped or the like, and self-assembled to make the coating and the cathode wire substrate more firmly bonded, and form a dense ceramic coating with a nanostructure on the surface of the cathode wire substrate, which can cover and protect the surface of the cathode wire, greatly improving the corrosion resistance of the cathode wire and reducing the risk of the cathode wire falling off.
[0031] 8. The coating should be applied within 48 hours after phosphating treatment to avoid re-oxidation of the treated surface and affect the subsequent coating effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic structural diagram of a cathode wire for an electrostatic precipitator provided by the present invention;
[0033] Figure 2 A schematic diagram of a coating structure for a cathode wire of an electrostatic precipitator provided by the present invention;
[0034] Figure 3 This is a schematic diagram of the SEM microscopic morphology of the surface of the nano-ceramic coating in the present invention;
[0035] Figure 4 It is a schematic diagram of the cross-sectional morphology of the cathode line in the present invention;
[0036] Figure 5 This is a schematic diagram of the water contact angle of the nano-ceramic coating in Example 1 provided by the present invention.
[0037] In the figure: 1. Support round steel; 2. Needle punching; 3. Phosphate coating; 4. Nano-ceramic coating. DETAILED DESCRIPTION
[0038] The following is in conjunction with the preferred embodiment and with reference to the attached Figure 1-5 , the present invention is further described. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein; the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels; the experimental methods in the following examples, unless otherwise specified, are all conventional methods.
[0039] Example 1
[0040] This embodiment provides a method for preparing a cathode line for an electrostatic precipitator, comprising the following steps:
[0041] S1: pre-treating the cathode wire, and then phosphating the cathode wire to form a phosphating film with a microporous structure on its surface;
[0042] In this embodiment, the specific process of the phosphating treatment is: the cathode wire is immersed in a phosphating treatment solution at 30°C for 10 minutes, and after washing and drying, a phosphating film is formed on the surface of the cathode wire. The thickness of the phosphating film is 10 μm. The phosphating treatment solution is NO 3- / ClO 3- / NO 2- Accelerator system.
[0043] In this embodiment, the pretreatment step includes degreasing, pickling and water washing the cathode wire to remove rust, grease and oxide film on the surface of the cathode wire. The specific process of the pretreatment is as follows:
[0044] S11: Immerse the cathode wire in a first degreasing tank at 65°C for 6 minutes, then immerse it in a second degreasing tank for 3 minutes, and wash it twice with water to complete degreasing; the tank liquid in the degreasing tank is 50g / L of degreasing agent; to remove oil stains, waste dust and polishing ash on the surface of the cathode wire;
[0045] S12: Immerse the degreased and deoiled cathode wire in a pickling tank at 28°C for 1 minute to remove the oxide film on the surface and expose the clean activated surface of the cathode wire. After washing with water twice, the pickling treatment is completed.
[0046] S2: within 48 hours after the phosphating treatment, applying the nano-ceramic coating on the cathode wire treated in step S1, so that the nano-ceramic coating penetrates into the microporous structure of the phosphating film in a wet film state; the raw materials of the nano-ceramic coating include nano-particles, graphene and solvent;
[0047] In this embodiment, the nano ceramic coating is applied by a dipping process, wherein the cathode wire is immersed in the nano ceramic coating as a whole, and the coating on the flow edge is removed by lifting it up, and the coating is completed after natural drying.
[0048] In this embodiment, the nanoparticles are nano-silicon oxide particles and nano-titanium oxide particles mixed in a weight ratio of 5:1, and the solvent is anhydrous ethanol. The preparation process of the nano-ceramic coating is: nano-silicon oxide particles and nano-titanium oxide particles are mixed in a set ratio, anhydrous ethanol is added, and the mixture is stirred for 2 hours to obtain a nano-ceramic sol, and then graphene is added and dispersed for 30 minutes to obtain the nano-ceramic coating. In this embodiment, the graphene accounts for 3wt% of the nano-ceramic coating.
[0049] S3: baking the cathode wire treated in step S2 at 100° C. for 30 min to solidify the coating on the surface of the cathode wire to form a nano ceramic coating with a thickness of 20 μm, thereby obtaining the cathode wire for the electrostatic precipitator.
[0050] The cathode line prepared in this embodiment is as follows Figure 1 As shown, the cathode wire includes a supporting round steel 1 and a plurality of needles 2 welded on the supporting round steel 1. Figure 2 As shown, the surfaces of the supporting round steel 1 and the needle 2 are provided with a phosphate film 3, and the surface of the phosphate film 3 is provided with a nano-ceramic coating 4.
[0051] In this embodiment, the SEM morphology of the surface of the nano-ceramic coating is as follows: Figure 3 As shown, from Figure 3 It can be seen that after the composite nanosol is mixed, the nanoparticles form a dense coating on the substrate surface after self-assembly.
[0052] The cross-sectional morphology of the cathode line prepared in this embodiment is as follows Figure 4 As shown, from Figure 4 It can be seen that the coating forms a strong bond with the substrate and the coating thickness is 20 μm.
[0053] like Figure 5 As shown, in this embodiment, the water contact angle of the nano-ceramic coating is 110°, and the modified nanoparticles are attached to the surface of the coating, which increases the roughness of the coating. According to the Wenzel model, the presence of the rough surface makes the actual solid-liquid contact area larger than the apparent geometric contact area, which geometrically enhances the hydrophobicity. At the same time, the hydrophobic functional groups grafted on the surface of the nanoparticles reduce the surface tension and improve the hydrophobic properties of the coating.
[0054] Example 2
[0055] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0056] In this embodiment, the nanoparticles are nano-silicon oxide particles, nano-titanium oxide particles and nano-aluminum oxide particles mixed in a weight ratio of 8:1:1, and graphene accounts for 1wt% of the nano-ceramic coating; in step S3, the baking temperature is 90°C, the baking time is 40min, and the thickness of the formed nano-ceramic coating is 10μm.
[0057] Example 3
[0058] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0059] In this embodiment, the nanoparticles are obtained by mixing nano silicon oxide particles and nano zirconium oxide particles in a weight ratio of 4:1, and the solvent is n-octane; in step S3, the baking time is 20 minutes, and the thickness of the formed nano ceramic coating is 50 μm.
[0060] Example 4
[0061] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0062] In this embodiment, the nanoparticles are nano-silicon oxide particles and nano-titanium oxide particles mixed in a weight ratio of 5:1, and the solvent in the nano-ceramic coating is toluene; in step S3, the baking temperature is 120°C, and the thickness of the formed nano-ceramic coating is 15 μm.
[0063] Example 5
[0064] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0065] In step S2 of this embodiment, the nano ceramic coating is applied by spraying, the spray room temperature is 25°C, the humidity condition is 60% RH, the spray pressure is 4.5 bar, the gun distance is 15 cm, and the spray flow rate is 60 CC / min. In the nano ceramic coating, the solvent is methanol; the thickness of the formed nano ceramic coating is 30 μm.
[0066] Example 6
[0067] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0068] In this embodiment, the nanoparticles are single nano silicon oxide particles.
[0069] Example 7
[0070] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0071] In this embodiment, graphene accounts for 5wt% of the nano-ceramic coating.
[0072] In an embodiment of the present invention, the solvent can also be selected from one or a combination of anhydrous ethanol, methanol, isopropanol, n-heptane, n-octane, benzene, toluene, xylene, ethylbenzene, and naphtha; the nanoparticles can also be selected from one or a combination of nano-alumina particles, nano-titanium oxide particles, nano-zirconium oxide particles, and nano-silicon oxide particles.
[0073] Example 8
[0074] This embodiment provides a method for preparing cathode wires for an electrostatic precipitator, which is basically the same as that of Embodiment 1, except that:
[0075] In this embodiment, the nano-ceramic coating does not contain graphene.
[0076] Comparative Example 1
[0077] The difference from Example 1 is that in step S3 of this comparative example, the baking temperature is 70° C. and the baking time is 30 min.
[0078] Comparative Example 2
[0079] The difference from Example 1 is that in step S1 of this comparative example, the cathode line is not subjected to phosphating treatment.
[0080] Comparative Example 3
[0081] The difference from Example 1 is that the coating used in step S2 of this comparative example is a common silicone coating.
[0082] Implementation effect evaluation
[0083] The excellent effects achieved by the present invention are further illustrated by conducting specific tests on the cathode wires prepared in Examples 1-8 and Comparative Examples 1-3.
[0084] Hardness test: The hardness of the sample is tested in accordance with GB / T 6739-1996 "Coating hardness pencil test method";
[0085] Hydrophobic angle test: According to the relevant standards of ASTM D7334, the test is carried out using a water drop angle tester;
[0086] Specific resistance test: Tested according to the relevant standards of GB / T 1410-2006;
[0087] Neutral salt spray test: The test was conducted in accordance with the national standard GB / T 10125-1997 "Artificial atmosphere corrosion test salt spray test", where the salt spray test medium was 5wt% NaCl solution and the test room temperature was set at 35°C;
[0088] Coating adhesion test: Coating adhesion test is carried out according to GB / T 9286-1988 "Coating adhesion test for paints and varnishes - cross-cut method".
[0089] The test results are shown in the table below:
[0090] Table 1 Performance test results statistics
[0091]
[0092]
[0093] It can be seen from the above table that the cathode wire prepared by the preparation method of the cathode wire for an electrostatic precipitator provided by the present invention has excellent dirt resistance and corrosion resistance. The nano-ceramic coating of the present invention has strong adhesion, high hardness, good hydrophobicity and wear resistance, and is suitable for use as a cathode wire to improve the anti-dust accumulation and corrosion resistance of the cathode wire.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing cathode wires for an electrostatic precipitator, characterized in that: The following steps are involved: S1: Phosphating the cathode wire to form a phosphating film with a microporous structure on its surface; S2: coating the nano-ceramic coating on the cathode wire treated in step S1, so that the nano-ceramic coating penetrates into the microporous structure of the phosphating film in a wet film state; the raw materials of the nano-ceramic coating include nano-particles and solvents; S3: baking the cathode wire treated in step S2 at 90-120° C. for 20-40 min to solidify the coating on the surface of the cathode wire to form a nano ceramic coating with a thickness of 10-50 μm, thereby obtaining the cathode wire for the electrostatic precipitator.
2. The method for preparing a cathode line for an electrostatic precipitator according to claim 1, characterized in that: In step S1, before the cathode wire is subjected to phosphating treatment, the cathode wire is also subjected to pretreatment, wherein the pretreatment includes degreasing and oil removal, pickling treatment and water washing of the cathode wire to remove rust, grease and oxide film on the surface of the cathode wire. The specific process of the pretreatment is as follows: S11: immerse the cathode wire in a first degreasing tank at 65°C for 6 minutes, then immerse it in a second degreasing tank for 3 minutes, and wash it twice to complete degreasing; the tank liquid in the degreasing tank is 50g / L of degreasing agent; S12: Immerse the degreased and deoiled cathode wire in a pickling tank at 28°C for 1 minute, and then rinse with water twice to complete the pickling treatment.
3. The method for preparing cathode wires for an electrostatic precipitator according to claim 1, characterized in that: In step S2, the nanoparticles are one or a mixture of nano-aluminum oxide particles, nano-titanium oxide particles, nano-zirconium oxide particles, and nano-silicon oxide particles.
4. The method for preparing a cathode line for an electrostatic precipitator according to claim 3, characterized in that: The nanoparticles are a mixture of nano-silicon oxide particles and one or more of nano-aluminum oxide particles, nano-titanium oxide particles, and nano-zirconium oxide particles. The weight ratio of the nano-silicon oxide particles to the other nanoparticles is (1-8):
1.
5. The method for preparing cathode wires for an electrostatic precipitator according to claim 3, characterized in that: The nanoparticles are a mixture of nano silicon oxide particles and nano titanium oxide particles, and the weight ratio of the nano silicon oxide particles to the nano titanium oxide particles is 5:
1.
6. The method for preparing cathode wires for an electrostatic precipitator according to claim 1, characterized in that: The raw materials of the nano ceramic coating also include a thin layer of graphene, and the mass percentage of the graphene in the nano ceramic coating is 1-5wt%.
7. The method for preparing cathode wires for an electrostatic precipitator according to claim 1, characterized in that: The solvent is one or a combination of anhydrous ethanol, methanol, isopropanol, n-heptane, n-octane, benzene, toluene, xylene, ethylbenzene and naphtha.
8. The method for preparing cathode wires for an electrostatic precipitator according to claim 1, characterized in that: In step S2, the coating is applied within 48 hours after the phosphating treatment.
9. A cathode wire for an electrostatic precipitator, characterized in that: The cathode wire is prepared according to the method for preparing a cathode wire for an electrostatic precipitator according to any one of claims 1-8.
10. The cathode wire for an electrostatic precipitator according to claim 9, characterized in that: The cathode wire comprises a supporting round steel and a plurality of needles welded on the supporting round steel. The surfaces of the supporting round steel and the needles are provided with a phosphating film, and the surface of the phosphating film is provided with a nano ceramic coating.
Citation Information
Patent Citations
Ash deposition prevention cathode wire for electric dust remover
CN114100859A
A coating cathode wire and electrostatic spraying method thereof
CN115213014B
Hot-dip galvanizing cathode wire of electric precipitator and preparation method of hot-dip galvanizing cathode wire
CN116571353A
Cathode wire for electric dust remover
CN201308861Y